2021
DOI: 10.3390/s21165478
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Scheduling Optimization Model Based on Variable Speed in a Seaport with One-Way Navigation Channel

Abstract: To improve the efficiency of in-wharf vessels and out-wharf vessels in seaports, taking into account the characteristics of vessel speeds that are not fixed, a vessel scheduling method with whole voyage constraints is proposed. Based on multi-time constraints, the concept of a minimum safety time interval (MSTI) is clarified to make the mathematical formula more compact and easier to understand. Combining the time window concept, a calculation method for the navigable time window constrained by tidal height an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…The WSSP was extended by introducing a triangular fuzzy number and a method for determining the feasible navigable time window of a vessel subject to the tide height constraint. Liu et al, (2021b) considered the characteristics of variable vessel speeds and proposed a speed-constrained scheduling method based on time window.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The WSSP was extended by introducing a triangular fuzzy number and a method for determining the feasible navigable time window of a vessel subject to the tide height constraint. Liu et al, (2021b) considered the characteristics of variable vessel speeds and proposed a speed-constrained scheduling method based on time window.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the precise algorithms take long computational time, and it is difficult to obtain a global optimal solution even for small-scale calculation examples. Therefore, heuristic methods are proposed to solve the problem, including a simulated annealing multi-population genetic algorithm [6], a simulated annealing algorithm [7,8], and a hybrid algorithm combining heuristic rules and simulated annealing algorithm [9], a meta-heuristic algorithm [10,11,12], a non-dominated sorting genetic algorithm [13,14], a genetic algorithm [16,17,18], a tabu search algorithm [19], a large neighborhood search algorithm [15]. Although showing much attractiveness in ship scheduling optimization, previous studies still revealed some concerns of which the theoretical implications have yet been well addressed in the existing literature.…”
Section: Introductionmentioning
confidence: 99%